Pembelajaran Sejarah Berwawasan Lingkungan sebagai upaya Menumbuhkan Kesadaran Lingkungan Siswa SMA - Anggriani, Ni Ketut; Supriatna, Nana; Tarunasena, Tarunasena (Universitas Hamzanwadi, 2025)
Everyone should have environmental awareness, but in reality, this is not evident, as reflected in the indifference shown when littering and a lack of empathy towards the surrounding environment and environmental issues. This article aims to explain the importance of fostering environmental awareness among students through environmentally conscious history education. It is hoped that students will be able to understand the root causes of environmental issues occurring around them and the impacts they may cause. Students can also learn from history how environmental solutions can be applied in the present by adapting to the spirit of the times. The method used to compile this article is a descriptive qualitative method with a literature review approach, using relevant sources from journals, books, and other written materials. Pembelajaran sejarah berwawasan lingkungan is an integrated effort to provide a broad understanding of environmental history and its significance for human life. Therefore, fostering environmental awareness is one of the responsibilities of history education, making environmental issues a focus of study that can be integrated into history education. In its implementation, pembelajaran sejarah berwawasan lingkungan can utilise the problem-based learning model, enabling students to analyse the causes of environmental issues resulting from human activities in the past that impact the present, and to identify solutions for current problems that can be derived from past experiences and adapted to the current environmental conditions. This approach aims to create contextual and easily understandable learning experiences, ultimately leading to enhanced environmental awareness among students.